Victim and villain: ambiguous experience of nursing students in the university context - Luma Costa Pereira Peixoto; Evangelia Kotzias Atherino dos Santos; Luana Machado Andrade; Patrícia Anjos Lima de Carvalho; Edite Lago da Silva Sena (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To understand how Undergraduate Nursing Students signify the university context. Method A qualitative research, of a phenomenological nature, based on the ontology of Maurice Merleau-Ponty, with the participation of 41 undergraduate nursing students from a public university in the interior of Bahia, Brazil. Data were collected from February to April 2019, using four wheels of Community Therapy, whose produced material was submitted to the Analytical of Ambiguity technique. Results From the analysis of the experiential descriptions, two categories emerged that reveal the significance attributed by students to their experiences in the university context: the university that generates suffering and the university that provides growth. Final considerations Undergraduate Nursing students signify the university context as an ambiguous experience, at the same time that the university is seen as generating suffering, it is also seen as capable of providing intellectual, sociocultural, affective and political growth.